1976
DOI: 10.1002/pol.1976.170141015
|View full text |Cite
|
Sign up to set email alerts
|

Formation of free radicals in photoirradiated cellulose. VIII. Mechanisms

Abstract: SynopsisPhotoinduced free radicals in cellulose were studies by means of ESR spectroscopy. Plausible mechanisms have been suggested for each type of intermediate radical to account for the ESR spectra observed and for the product balances. Based on the principles of photochemistry of cellulose, coupled with the findings of the ESR spectra, it becomes evident that localization of the energy absorbed in the cellulose molecule leads to formation of free radicals in terms of chain scission, dehydrogenation, dehydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 61 publications
1
25
0
Order By: Relevance
“…The established radical II has increased hyperfine interaction withp rotons (A H˛³ 2.2 mT) and less withˇprotons. 22 It was suggested that the radicals V and VI have similar hyperfine interactions with˛protons with an accuracy of 0.2-0.3 mT. The interaction withˇprotons gives a HFS with the hyperfine constant near 0.4-0.5 mT (doublet for V and triplet for VI radicals), which cannot be resolved because of the large (up to 1 mT) electron-˛proton dipole-dipole interaction causing an additional inhomogeneous line broadening.…”
Section: Cellulosementioning
confidence: 98%
See 3 more Smart Citations
“…The established radical II has increased hyperfine interaction withp rotons (A H˛³ 2.2 mT) and less withˇprotons. 22 It was suggested that the radicals V and VI have similar hyperfine interactions with˛protons with an accuracy of 0.2-0.3 mT. The interaction withˇprotons gives a HFS with the hyperfine constant near 0.4-0.5 mT (doublet for V and triplet for VI radicals), which cannot be resolved because of the large (up to 1 mT) electron-˛proton dipole-dipole interaction causing an additional inhomogeneous line broadening.…”
Section: Cellulosementioning
confidence: 98%
“…22,23 Nevertheless, ESR experiments of pure cellulose were separately carried out because of the expected different results connected with using short UV wavelength (248 nm) and larger power of illumination, in contrast to results obtained before (e.g. Ref.…”
Section: Cellulosementioning
confidence: 99%
See 2 more Smart Citations
“…This degrading effect on cotton was noticed over a century ago. Electron spin resonance study of light -irradiated cotton has established the reason of degradation as free -radical generation on cellulose [2,3] . An understanding of this phenomenon has also opened up possibilities for improvement of the properties of cotton fabric by grafting a variety of monomers onto it [3 -5] .…”
Section: Grafting On Cottonmentioning
confidence: 99%